Modernisasi Sistem Pendidikan Pesantren - Marzuki, Marzuki; Usman, Usman; Amin, Muhammad (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
Islamic boarding schools are a type of traditional Indonesian Islamic education to deepen Islamic religious knowledge and practice it as a guide to daily life. Islamic boarding schools have existed for hundreds of years and have reached almost all levels of Muslim society. Islamic boarding schools have been recognized as educational institutions that have contributed to the intellectual life of the nation. During the period of colonialism, Islamic boarding schools were religious educational institutions that contributed greatly to society in enlightening the world of education. Not a few national leaders who participated in proclaiming this nation's independence were alumni or at least had studied at Islamic boarding schools. However, now the reputation of the pesantren seems to be being questioned by parts of the Indonesian Muslim community. The majority of pesantren today seem to be in an ivory tower, elitist, far from social reality. This problem of socialization and actualization is compounded by scientific problems, namely gaps, alienation and differentiation between Islamic boarding school scholarship and the modern world. So that sometimes pesantren graduates are unable to compete or are not ready to compete with general graduates in matters of professionalism in the world of work. The world of Islamic boarding schools is faced with the problems of globalization, which certainly carry a heavy burden of responsibility for Islamic boarding schools